2010
DOI: 10.1007/s11899-010-0053-y
|View full text |Cite
|
Sign up to set email alerts
|

Anti-CD30 Antibodies for Hodgkin Lymphoma

Abstract: Treatment of refractory or relapsed classical Hodgkin lymphoma (HL) remains challenging, but targeted immunotherapy has recently emerged as a potential treatment option for these patients. Although first-generation monoclonal anti-CD30 antibodies proved disappointing, current efforts to modify anti-CD30 antibodies to improve binding of effector cells and enhance activity appears more promising, as does the development of novel antibody-drug conjugates (ADCs). ADCs offer the potential to deliver potent therapie… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
49
0
1

Year Published

2010
2010
2019
2019

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 48 publications
(50 citation statements)
references
References 39 publications
0
49
0
1
Order By: Relevance
“…This trial was reported in 1992 and no further trials were reported. Because of the similar antigen of BER-H2-Sap6 and Ki-4.dgA, their performance has been compared [191] …”
Section: Ber-h2-sap6mentioning
confidence: 99%
“…This trial was reported in 1992 and no further trials were reported. Because of the similar antigen of BER-H2-Sap6 and Ki-4.dgA, their performance has been compared [191] …”
Section: Ber-h2-sap6mentioning
confidence: 99%
“…3,4 Different companies use different strategies: Roche (Basel, Switzerland), in cooperation with Glycart (Schlieren, Switzerland), has developed an improved, glyco-engineered CD20 antibody, termed GA101. 5 Two other antibodies directed to the lymphoma-associated antigens CD19 (XmAb5574) 6,7 and CD30 (XmAb2513), 8 developed by Xencor (Monrovia, CA, USA), carry the amino-acid exchanges S239D and I332E (SDIE modification). All these antibodies were reported to exert markedly enhanced ADCC.…”
Section: Introductionmentioning
confidence: 99%
“…One Newer generation of anti-CD30 antibodies with enhanced Fc receptor-antibody activity (Medarex, MDX-1401 ) and with antibody-drug conjugates are currently under study (Foyil and Bartlett 2010).…”
Section: Antibody/receptor Therapymentioning
confidence: 99%